DETERMINANT OF HUMAN DEVELOPMENT INDEX: CAPITAL EXPENDITURE AS A MEDIATING VARIABLE - Raulita Ramadina Putri Febrian; Dwi Suhartini (International Journal of Economy, Education and Entrepreneurship, 2023)
This study aims to determine, through quantitative methods, the relationship between the Physical and Non-physical Special Allocation Funds and the Human Development Index, with capital expenditure as the mediating variable. The sample used in the study was 105 data consisting of districts and cities in the Maluku region in Maluku and North Maluku Provinces from 2018 to 2022. The research methods used are multiple linear regression and path analysis. The hypothesis testing results show that Physical SAF affects capital expenditure, Non-physical SAF has no effect on capital expenditure, Physical SAF adversely impacts HDI, Non-physical SAF and Capital Expenditure both affect HDI, and Capital Expenditure can mediate the relationship between Physical SAF and HDI. However, Capital Expenditure cannot mediate the relationship between Non-physical SAF and HDI